(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
In this article it’s given wide range of information about the neccessaty of establishment of psychological service in the branch of phthisiology and the importance of psychological practice in medicine. It is also suggested to create psychological practical program about how to cure and overcome efficiently taking into the consideration patients psychological situations who have tuberculosis.